Moral Topology and the Making of Cosmological Boundaries: The Case of Neo-Pentecostal Exorcism in Brazil. Issue 3 (1st September 2019) - Shapiro, Matan
Abstract : Seeking to uproot evil from people's life, neo-Pentecostal exorcists in Brazil separate between internal and external bodily surfaces and then 'close' the victim's entire body to protect against further malignant intrusion. Based on fieldwork in Brazil and the analysis of expulsion videos online, I demonstrate that exorcists self-consciously use topological imaginaries of connectedness and disjunction to generate a reality in which demons and humans occupy mutually exclusive ontological domains. I argue that the moral transformation that these rituals encourage is thus contingent on the successful disentanglement of bodily surfaces, which distinguishes inside from outside and humans from demons. I use the term 'moral topology' to analyze this process and call for further cross-cultural attention to the ethnographic vitality of topological imaginaries in the making of cosmological boundaries.